Bioinspired Microenvironments: Rational Design of High‐Mobility Semicrystalline Conjugated Polymers with Tunable Charge Polarity: Beyond Benzobisthiadiazole‐Based Polymers (Adv. Funct. Mater. 2/2017). (January 2017) - Wang, Yang; Hasegawa, Tsukasa; Matsumoto, Hidetoshi; Mori, Takehiko; Michinobu, Tsuyoshi
Abstract : High‐mobility semiconducting polymers for thin film transistors are reported by T. Michinobu and co‐workers on page 1604608. The polymers contain strong electronaccepting thiadiazolobenzotriazole units, highly planar vinylene spacers, heteroatom‐substituted aromatic rings, and solubilizing alkyl groups. They show p‐type transistor behavior with a remarkably high hole mobility of 3.22 cm 2 V −1 s −1 as well as n‐type dominant ambipolar behavior.